2014
DOI: 10.1002/cam4.353
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and metabolic effects of metformin in a preoperative window clinical trial for endometrial cancer

Abstract: We conducted a preoperative window study of metformin in endometrial cancer (EC) patients and evaluated its antiproliferative, molecular and metabolic effects. Twenty obese women with endometrioid EC were treated with metformin (850 mg) daily for up to 4 weeks prior to surgical staging. Expression of the proliferation marker Ki-67, estrogen receptor (ER), progesterone receptor (PR), adenosine monophosphate-activated protein kinase (AMPK), and downstream targets of the mammalian target of rapamycin (mTOR) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 61 publications
(90 reference statements)
8
102
0
2
Order By: Relevance
“…In preclinical studies, metformin was found to inhibit tumour spread and to reduce tumour growth 23,24 . In short-term window-of-opportunity studies, metformin was shown to affect tumour growth both through indirect, insulin-dependent pathways 6,7,25 and by activating ampk pathways to directly affect cancer cells 26,27 . However, in larger epidemiologic studies, those actions have not translated into an improvement in tumour stage or cancer burden for either breast cancer or other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, metformin was found to inhibit tumour spread and to reduce tumour growth 23,24 . In short-term window-of-opportunity studies, metformin was shown to affect tumour growth both through indirect, insulin-dependent pathways 6,7,25 and by activating ampk pathways to directly affect cancer cells 26,27 . However, in larger epidemiologic studies, those actions have not translated into an improvement in tumour stage or cancer burden for either breast cancer or other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…phase 0) trials have been conducted to evaluate metformin administration in the time window between cancer diagnosis and surgery. These studies show mixed results for tumor p-AMPKα at Thr172 expression before and after metformin use (ranging from 850–2250 mg/day): p-AMPKα protein expression was increased in one study of endometrial cancer patients (121), decreased in another study of endometrial cancer patients (122), and unchanged in two studies of endometrial (123) and prostate (124) cancer patients. Thus, a direct link between short-term metformin use and AMPK activation in targeted tissue is unclear.…”
Section: Ampk Role In Cancer: Human Studiesmentioning
confidence: 99%
“…Многие терапевтические эффекты метформина объясняются его активирующим влиянием на АМФ-активируемую протеинкиназу, которая определяет энергетический статус клетки [4,31]. Действуя на АМФ-ПК, метформин в то же время является ингибитором инициации трансляции [32].…”
Section: метформин как активатор мар-киназыunclassified
“…Интересно, что метформин превентирует развитие не только рака кишечника, но и уменьшает развитие до-брокачественных новообразований толстой кишки [2]. Авторы показали, что метформин уменьшает пролифера-цию опухоли в эндометрии [4]. Также описано, что при-менение метформина снижает заболеваемость раком поджелудочной железы [5].…”
unclassified